Morgellons Disease Presenting As an Eyelid Lesion. Issue 4 (July 2016) - Sandhu, Rasanamar K.; Steele, Eric A.
Abstract : Morgellons disease is characterized by complaints of uncomfortable skin sensations and fibers emanating from nonhealing skin lesions. Morgellons disease is well-known in the dermatology and psychiatry literature, where it is typically considered a subtype of delusional parasitosis, but it has not yet been described in the ophthalmology literature. A patient with self-reported Morgellons disease is presented, who was referred for evaluation of left lower eyelid ectropion. She reported that her skin was infested with fibers that were "trying to get down into the eyelid." On examination, she had ectropion of the left lower eyelid, broken cilia, and an ulcerated left upper eyelid lesion concerning for carcinoma. Biopsy of the lesion was consistent with excoriation. Treatment of her ectropion was deferred out of concern for wound dehiscence, given the patient's aggressive excoriation behavior. This case is presented to make the ophthalmologist aware of this disorder and to highlight the appropriate clinical management. Abstract : A patient with the diagnosis of Morgellons Disease presented for evaluation of a skin lesion with an appearance suspicious for carcinoma. The background of the disease is discussed, as well as the challenges in managing patients with symptoms of delusional parasitosis.